A Prey‐Predator Model of Trade Union Density and Inequality in 12 Advanced Capitalisms over Long Periods. (February 2017) - Chauvel, Louis; Schröder, Martin
Summary: This article shows empirically how trade union membership and income inequality are mutually related in twelve countries over more than 100 years. While past research has shown that high income inequality occurs alongside low trade union membership, we show that past income inequality actually increases trade union membership with a time lag, as trade unions recruit more members after inequality has been high. But we also show that strengthened trade unions then fight inequality, thereby destroying what helped them to recruit new members in the past. As trade union density decreases, inequality increases and eventually re‐incentivises workers to join unions again. By showing this empirically, we reconceptualise the relationship between inequality and union density as a prey and predator model, where predators eat prey – unions destroy inequality, but thereby also destroy their own basis for survival. By empirically showing that trade union density and social inequality influence each other in this way over long periods, this article contributes to a dynamic approach on how social problems and social movements interact.